Preliminary investigations into developing all‐D Omiganan for treating Mupirocin‐resistant MRSA skin infections. (11th July 2017) - Ng, Siew Mei Samantha; Teo, Shu Wei; Yong, Yaqing Elena; Ng, Fui Mee; Lau, Qiu Ying; Jureen, Roland; Hill, Jeffrey; Chia, C. S. Brian
Abstract : Staphylococcus aureus is the primary pathogen responsible for the majority of human skin infections, and meticillin‐resistant S. aureus (MRSA) currently presents a major clinical concern. The overuse of Mupirocin, the first‐line topical antibacterial drug over 30 years, has led to the emergence of Mupirocin‐resistant MRSA, creating a clinical concern. The antimicrobial peptide Omiganan was touted to be a promising antibacterial drug candidate due to its rapid membrane‐disrupting bactericidal mode of action, entering clinical trials in 2005 as a topical gel to prevent catheter site infections. However, drug development ceased in 2009 due to a lack of efficacy. We postulate this to be due to proteolytic degradation caused by endogenous human skin proteases. Herein, we tested our hypothesis using Omiganan and its all‐ D enantiomer in a human skin protease stability assay, followed by anti‐MRSA activity assay against of a panel of clinical MRSA isolates, a bactericidal/static determination and a time‐kill assay to gauge all‐ D Omiganan's potential for further topical antibacterial drug development. Abstract : Herein, we compared the skin protease stability and antibacterial activity of Omiganan, an antimicrobial peptide, to its all‐ D enantiomer. Results revealed that the latter was proteolytically more stable while possessing the same antibacterial potency, suggesting that the all‐D peptide may be better suited as a topical drug development candidate.